Bolivia: Agricultural R&D indicators factsheet - Stads, Gert-Jan; de los Santos, Luis (International Food Policy Research Institute, 2023)
Bolivia’s agricultural R&D spending is characterized by considerable year-toyear fluctuations. The costs of R&D programs, running the day-to-day operations of laboratories, and muchneeded capital investments are chiefly funded by donors and development banks. Dependence on this type of funding—which by nature is volatile and ad hoc—makes the country somewhat vulnerable to funding shocks. Bolivia’s agricultural research spending has not kept pace with growth in agricultural output. The country’s agricultural research intensity ratio—that is agricultural research spending as a percentage of agricultural GDP—halved from 1.0 to 0.5 percent during 2015–2020. Bolivia’s agricultural research investment is too low to effectively address farm productivity challenges of the rural poor and threats posed by climate change. Compared with most countries in South America, Bolivian agricultural R&D agencies employ relatively few researchers with PhD degrees. In addition, a considerable portion of the most highly qualified researchers are set to retire in the coming decade. The country will need to recruit and train the next generation of agricultural researchers without delay and provide the necessary conditions to maintain their commitment over time.